Sikap dan tindakbalas penghuni bangunan dalam menghadapi situasi kebakaran kajian kes : Menara Ansar, Johor Bahru - Mohd. Khudzairi, Nawal (2007)
Today most buildings are equipped with adequate fire safety systems. But still,a Malaysia losing RM4.2 billion due to fire since the last decade. During a fire, problems usually arise because systems were put in place but with false expectations regarding how occupants actually behave during fires. The observation that occupants tend to ignore the sound of the fire alarm in large public buildings such as shopping centers, continuing their normal activities should be taken into account. In office buildings, well designed fire doors have failed to fulfil their role because occupants have installed door stops to facilitate free movement in everyday use. Thus in the event of a fire, the doors stay open. Many of these problems could be foreseen if more attention were given to human behaviour in fire. There are number of factors that could have impact on occupant response and behaviour. These factors are related to the occupants characteristic, the building characteristic and the fire itself. Consideration should be given to interplay of this factors to gain a better understanding of human behaviour in fire and to improve the design and implementation of fire safety systems in builidngs. The objectives of this research are (1) to identify the factors that have impact on occupant behaviour during fire. (2) To identify the requirement implement the fire management plan based on the occupants behaviour. To attain these objectives, data are collected by interviewing Damansara Assets Sdn Bhd, the management of Menara Ansar and distributing questionnaires to the Menara Ansar building occupants. Data collected are analysed by the frequency analysis method using min comparison analysis. From the analysis, the factors which have impact on the human behaviour during fire have been identified. Among the identified factors are, gender, age, training, experience and assumed role in the building. Seven steps in implementing the fire management plan incorporating with objectives of the building management of Menara Ansar have been listed. The awareness of the fire safety should begin with the building management initiative to implement the fire safety policy. As for that, this comprehensive overview of the plan shall act as a tool for a shift in paradigm towards the establishment of safe and healthy workplace environment.